2009
DOI: 10.9744/scriptura.2.1.56-62
|View full text |Cite
|
Sign up to set email alerts
|

Menakar Kekuatan Dan Keunggulan Industri Televisi Lokal Di Era Otonomi

Abstract: Keywords: television, industrialization, investor PENDAHULUANMesti diakui, jika perkembangan televisi dalam kurun dua dasawarsa belakangan ini luar biasa pesatnya. Tidak saja dilihat dari kuantitas stasiun televisinya, tetapi yang jauh lebih penting adalah pengaruh apa yang ditimbulkan akibat siaran tabung audio visual tersebut. Karakteristik pengaruh sesungguhnya adalah refleksi paling aktual atas jenis atau siaran apa yang diproduksi masing-masing stasiun televisi itu. Itu sebabnya semakin banyak institusi p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A number of studies have revealed how local television stations package their broadcasts as an attraction to grab viewers' attention. Priyowidodo (2009) reveals some examples from local television stations such as Bali TV, Yogya TV, and Borobudur TV very clearly directed the broadcast to audience segments which are bounded by local culture. Similarly, Favorite TV (Padang) for example also worked on Minang typical broadcast customs so that interested viewers and small-scale advertising can enter.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have revealed how local television stations package their broadcasts as an attraction to grab viewers' attention. Priyowidodo (2009) reveals some examples from local television stations such as Bali TV, Yogya TV, and Borobudur TV very clearly directed the broadcast to audience segments which are bounded by local culture. Similarly, Favorite TV (Padang) for example also worked on Minang typical broadcast customs so that interested viewers and small-scale advertising can enter.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies of similar themes have been carried out related to local television from various perspectives. Among other things, Priyowidodo conducted research on measuring the strength and the excellence of the local television industry in the era of autonomy (Priyowidodo, 2008). Priyowidodo stated that the era of regional autonomy which blew in the early days of the reformation gave fresh air to television.…”
Section: Introductionmentioning
confidence: 99%
“…The few conglomerates who have at the same time several national television stations are suspected to be the cause of the oligopoly of information in the community (Priyowidodo, 2008). The communities are nationally fed by less-quality programs such as soap operas and the advertisements that campaign for consumerism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Favorit TV (Padang) features a special broadcast of Minang customs. TV Manado and TOP (TV Orang Papua), program the characteristics of local humor, based on the region, in order to attract the viewers' attention [4].…”
Section: Introductionmentioning
confidence: 99%